Highly Stretchable, Adaptable, and Durable Strain Sensing Based on a Bioinspired Dynamically Cross‐Linked Graphene/Polymer Composite. Issue 19 (8th April 2019) - Lin, Shuyuan; Zhao, Xuanliang; Jiang, Xin; Wu, Anqi; Ding, Hanlin; Zhong, Yujia; Li, Jing; Pan, Jialiang; Liu, Bin; Zhu, Hongwei
Abstract: Flexible strain sensors can detect physical signals (e.g., temperature, humidity, and flow) by sensing electrical deviation under dynamic deformation, and they have been used in diverse fields such as human motion detection, medical care, speech recognition, and robotics. Existing sensing materials have relatively low adaptability and durability and are not stretchable and flexible enough for complex tasks in motion detection. In this work, a highly flexible self‐healing conductive polymer composite consisting of graphene, poly(acrylic acid) and amorphous calcium carbonate is prepared via a biomineralization‐inspired process. The polymer composite shows good editability and processability and can be fabricated into stretchable strain sensors of various structures (sandwich structures, fibrous structures, self‐supporting structures, etc.). The developed sensors can be attached on different types of surfaces (e.g., flat, cambered) and work well both in air and under water in detecting various biosignals, including crawling, undulatory locomotion, and human body motion. Abstract : Inspired by mineralization in nature, a highly flexible conductive graphene/polymer composite is designed and prepared. The composite shows good editability and processability and is fabricated into stretchable strain sensors with high adaptability and durability, and is applied on different types of surfaces for complex motion detection.